The sustainable fashion community of practice: leveraging sustainable fashion in the context of Covid-19 - Forskitt, Rianna (2021)
The Geographies of our worlds fundamentally changed as the Covid-19 pandemic and its ensuing lockdowns set in across the globe. This thesis uses the sustainable fashion community of practice on Instagram as the empirical vessel through which to explore the changes that occurred during the pandemic. The ultimate aim of this thesis is to offer novel insights which are situated in the context of the pandemic about how a sustainable fashion agenda may be leveraged.